Pengaruh Inflasi dan Kebijakan Bank Indonesia Terhadap Stabilitas Ekonomi di Indonesia 2010-2023 - Tri Rahayu; Ranti Delima Tobing; Fitrawaty Fitrawaty; Chelsya Olyza Malau; Anggun Sibarani (CV. Ulil Albab Corp, 2024)
The purpose of this study is to see how Indonesia's financial system stability index is affected by inflation and BI rate. The main concern raised is how changes in the benchmark interest rate and variations in inflation can affect the stability of the country's financial system and economy. Multiple regression analysis was used in this study using secondary data from Bank Indonesia reports and other relevant sources from 2010 to 2023. The calculated F value is smaller than the F table, indicating that there is no real relationship between the inflation rate and BI rate with the financial system stability index simultaneously. Based on the t value that does not exceed the t table, partial analysis shows that neither inflation nor BI rate has a significant effect on financial system stability. The regression coefficients of inflation and BI Rate are positive, but this does not support the hypothesis. The results of this study provide a valuable perspective for policymakers to design more efficient monetary tactics aimed at maintaining the stability of the Indonesian financial system. Hopefully, future studies on monetary policy and economic stability will use the results of this study as a reference.